2017
DOI: 10.1371/journal.pgen.1006851
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal orientation of microtubules controls conical cell shape in Arabidopsis thaliana petals

Abstract: The physiological functions of epidermal cells are largely determined by their diverse morphologies. Most flowering plants have special conical-shaped petal epidermal cells that are thought to influence light capture and reflectance, and provide pollinator grips, but the molecular mechanisms controlling conical cell shape remain largely unknown. Here, we developed a live-confocal imaging approach to quantify geometric parameters of conical cells in Arabidopsis thaliana (A. thaliana). Through genetic screens, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 66 publications
7
59
1
Order By: Relevance
“…2005). The microtubule-severing activity of KTN1 might even be regulated by AtROP2, AtROP4 and AtROP6 (Ren et al . 2017) via AtRIC1.…”
Section: Discussionmentioning
confidence: 99%
“…2005). The microtubule-severing activity of KTN1 might even be regulated by AtROP2, AtROP4 and AtROP6 (Ren et al . 2017) via AtRIC1.…”
Section: Discussionmentioning
confidence: 99%
“…As a proof-of-concept, we imaged microtubule reorganisation associated with regeneration of excised gametophore cells 15 in the microdevice. It is possible that the gametophore excision or injection in the microdevice transiently disrupts the microtubule arrays, based on low anisotropy values ( Figure 3E); however, the anisotropy score was eventually recovered to expected values for cortical microtubules [26][27][28] . Previous study demonstrated that gametophore cells regenerating as protonema produce certain signals, inhibiting protonema regeneration of the surrounding cells 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Anisotropy score ( Figure 3E) ranging from 0 (purely isotropic arrays) to 1 (purely anisotropic arrays) reflects the alignment of microtubules. For instance, anisotropy values for parallel microtubule arrays, such as cortical microtubules, typically range between 0.2-0.3 [26][27][28] . In our experiments, the initial values for anisotropy were lower than expected (0.09 ± 0.04 at time 0) and recovered in 3 h (0.2 ± 0.11).…”
Section: Observing Cytoskeleton Behaviour In Developmentmentioning
confidence: 99%
“…Similarly, spk1 and rop2 rop6 rop4RNAi mutants develop cells with wider tip angles. It was proposed that ROP2/6 and ROP4 regulate MTs via KTN1 (Ren et al, 2017). These new findings also suggest that ROP signaling networks play important and general roles in the regulation of cell expansion and cell shape; however, the precise regulatory mechanisms might be distinct in specific organs.…”
Section: Rop Function During Diffuse Growthmentioning
confidence: 93%